SNRK (Sucrose Nonfermenting 1-Related Kinase) Promotes Angiogenesis In Vivo. Issue 2 (February 2018) - Lu, Qiulun; Xie, Zhonglin; Yan, Chenghui; Ding, Ye; Ma, Zejun; Wu, Shengnan; Qiu, Yu; Cossette, Stephanie M.; Bordas, Michelle; Ramchandran, Ramani; Zou, Ming-Hui
Abstract : Objective—: SNRK (sucrose nonfermenting 1-related kinase) is a novel member of the AMPK (adenosine monophosphate-activated protein kinase)-related superfamily that is activated in the process of angiogenesis. Currently, little is known about the function of SNRK in angiogenesis in the physiological and pathological conditions. Approach and Results—: In this study, in Snrk global heterozygous knockout mice, retina angiogenesis and neovessel formation after hindlimb ischemia were suppressed. Consistently, mice with endothelial cell (EC)-specific Snrk deletion exhibited impaired retina angiogenesis, and delayed perfusion recovery and exacerbated muscle apoptosis in ischemic hindlimbs, compared with those of littermate wide-type mice. Endothelial SNRK expression was increased in the extremity vessel samples from nonischemic human. In ECs cultured in hypoxic conditions, HIF1α (hypoxia inducible factor 1α) bound to the SNRK promoter to upregulate SNRK expression. In the nuclei of hypoxic ECs, SNRK complexed with SP1 (specificity protein 1), and together, they bound to an SP1-binding motif in the ITGB1 (β1 integrin) promoter, resulting in enhanced ITGB1 expression and promoted EC migration. Furthermore, SNRK or SP1 deficiency in ECs ameliorated hypoxia-induced ITGB1 expression and, consequently, inhibited EC migration and angiogenesis. Conclusions—: Taken together, our data have revealed that SNRK/SP1-ITGB1 signaling axis promotes angiogenesis in vivo. Abstract : Supplemental Digital Content is available in the text.